A Different Comparison - Bouso García, Raquel (Buddhist Christian studies, 2026)
This article presents a critical examination of Perry Schmidt-Leukel's book, The Celestial Web, with a particular focus on the implications of the subtitle "Buddhism and Christianity: A Different Comparison." The article then asks what makes the proposed dialogue between the two religions different. Accordingly, the initial focus is on the recognition of otherness and plurality as they are embodied in the book's discourse, both at the interreligious and intrareligious levels, and also at the subjective level. Subsequently, an evaluation is conducted to ascertain the explanatory capacity of the fractal heuristic method, as proposed by the author. Finally, with respect to the subjects addressed in the book, issues are highlighted regarding the understanding of ultimate reality, interpretation, and language, as well as the logic of complementarity of opposites.